1978
DOI: 10.1128/iai.19.1.138-145.1978
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the role of cytophilic antibody in resistance to malaria parasites (Plasmodium berghei) in rats

Abstract: This paper reports the results of a study of the nature of the immune response against Plasmodium berghei parasites by inbred rats. A macrophage-cytophilic antibody specific for malarial antigens was identified and characterized. Detection of the antibody on the macrophage surface was accomplished by the parasite adherence tests and by the indirect fluorescent antibody technique. Isolation and purification of the macrophage-cytophilic and opsonic antibodies from hyperimmune rat serum was accomplished by QAE-Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…Absence of schizont ingestion was recorded when we used either 'immune monocytes' (Khusmith et al 1982) or in vitro armed monocytes. This is in agreement with the studies conducted by Kreier and co-workers using rat macrophages and P. berghei infected red cells (Chow & Kreier 1972, Green & Kreier 1978, Hamburger & Kreier 1976, Brooks & Kreier 1978, and contrasts with studies performed using mouse peritoneal macrophages and erythrocytes infected with P . berghei (Hunter et al 1979), P .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Absence of schizont ingestion was recorded when we used either 'immune monocytes' (Khusmith et al 1982) or in vitro armed monocytes. This is in agreement with the studies conducted by Kreier and co-workers using rat macrophages and P. berghei infected red cells (Chow & Kreier 1972, Green & Kreier 1978, Hamburger & Kreier 1976, Brooks & Kreier 1978, and contrasts with studies performed using mouse peritoneal macrophages and erythrocytes infected with P . berghei (Hunter et al 1979), P .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, immunoglobulins with antimalarial specificity were able to adhere to the monocytes and could be eluted from them. These cytophilic antibodies are probably attached via their Fc region to receptors on the surfaces ofmonocytes (Green & Kreier 1978, Berken & Benacerraf 1966.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the role of serum antibodies in P. berghei immunity (12,15,20,23,24,28,29,37,40,42). The passive transfer of immunity by lymphoid cells of rats recovered from P. berghei infection (17,37) was demonstrated to be due to B-type-antibody-producing lymphocytes (27).…”
Section: Discussionmentioning
confidence: 99%